Assessment of Dietary Bioactive Phenolic Compounds and Agricultural Sustainability of an African Leafy Vegetable Corchorus olitorius L. - Guzzetti, Lorenzo; Panzeri, Davide; Ulaszewska, Marynka; Sacco, Grazia; Forcella, Matilde; Fusi, Paola; Tommasi, Nicola; Fiorini, Andrea; Campone, Luca; Labra, Massimo (Frontiers in Nutrition, 2021)
Corchorus olitorius L. is an African leafy vegetable of high nutritional interest. To assess its agricultural suitability to sustainable cultivation conditions and its potential benefits for human nutrition, its phytochemicals content in response to conservation agriculture practices (i.e., no tillage and cover crop maintenance) and low water regime were evaluated and compared with response under conventional agriculture management. Hydric stress and no-tillage did not affect antioxidant metabolites content, compared to conventional agricultural practices. In both conditions, leaves were found to be a great source of phenolic compounds. The effect of these phenolic fractions was assessed on two colon cell phenotypes to evaluate putative nutraceutical properties. Polyphenols-enriched extracts (PEE) displayed selective cytotoxic activities against tumor Caco-2 cells but not on the healthy CCD841 line. PEE were able to trigger oxidative stress and to inhibit the activity of glutathione-independent antioxidant enzymes on Caco-2 cells. C. olitorius showed to be a promising crop for improving both agricultural sustainability and health benefits due to the great amount of antioxidant compounds in leaves, whose occurrence is not altered by stressful farming conditions. Given its high adaptability, the cultivation of this crop is therefore recommendable also in the Mediterranean basin.